A comparison study of plantar foot pressure in a standardized shoe, total contact cast, and prefabricated pneumatic walking brace - Baumhauer, J F; Wervey, R; McWilliams, J; Harris, G F; Shereff, M J (Foot & ankle international, 1997)
Total contact casting is the current recommended treatment for Wagner Stage 1 and 2 neuropathic plantar ulcers. The rationale for this treatment includes the equalization of plantar foot pressures and generalized unweighting of the foot through a total contact fit at the calf. Total contact casting requires meticulous technique and multiple cast applications to avoid complications before ulcer healing. An alternative to total contact casting is the use of a prefabricated brace designed to maintain a total contact fit. This study compares plantar foot pressure metrics in a standardized shoe (SS), total contact cast (TCC), and prefabricated pneumatic walking brace (PPWB). Five plantar foot sensors (Interlink Electronics, Santa Barbara, CA) were placed at the first, third, and fifth metatarsal heads, fifth metatarsal base, and midplantar heel of 10 healthy male subjects. Each subject walked at a constant speed over a distance of 280 meters in a SS, PPWB, and TCC. A custom-made portable microprocessor-based system, with demonstrated accuracy and reliability, was used to acquire the data. No significant differences in peak pressure or contact duration were found between the initial and repeat SS trials (P > 0.05). Peak pressures were reduced in the PPWB as compared to the SS for all sensor locations (P < 0.05). Similarly, peak pressures were reduced in the TCC compared to the SS for all sensor locations (P < 0.05) with the exception of the fifth metatarsal base (P = 0.45). Our results are summarized as follows: (1) the methods used in the current study were found to be reliable through a test-retest analysis; (2) the PPWB decreased peak plantar foot pressures to an equal or greater degree than the TCC in all tested locations of the forefoot, midfoot, and hindfoot; (3) compared to a SS, contact durations were increased in both the TCC and PPWB for most sensor locations; and (4) the relationship of peak pressure over time, the pressure-time integral, is lower in the brace compared to the shoe at the majority of sensor locations. The values are not significantly different between the cast and shoe. These findings suggest an unweighting of the plantar foot and equalization of plantar foot pressures with both the PPWB and TCC. Based on these findings, the PPWB may be useful in the treatment of neuropathic plantar ulcerations of the foot.